Effects of increasing monensin doses on performance of mid-lactating Holstein cows. Issue 1 (1st January 2019) - Santos, Mayara Celpf Bailoni; Araújo, Ana Paula Chaves; Venturelli, Beatriz Conti; Freitas, Jose Esler; Barletta, Rafael Villela; Gandra, Jefferson Rodrigues; de Paiva, Pablo Gomes; Acedo, Tiago Sabela; Rennó, Francisco Palma
ABSTRACT: The objective of this study was to determine the effect of increasing monensin doses on intake, nutrient digestion, ruminal fermentation, nitrogen balance, blood metabolites, milk yield and composition of lactating dairy cows. Twelve Holstein cows (135 ± DIM; 580 ± kg of BW) were assigned to three 4 × 4 Latin square design, with 21-d periods. Cows were randomly assigned within each square to receive one of the following treatments: Control (C): 0 mg kg −1 DM of monensin; Monensin 12 (M12): 12 mg kg −1 DM of monensin; Monensin 24 (M24): 24 mg kg −1 DM of monensin and Monensin 48 (M48): 48 mg kg −1 DM of monensin. Monensin had quadratic effect on intake of dry matter. Apparent total-tract digestibility of DM were similar between treatments; however, digestibility of CP increased. Monensin had no effect on ruminal pH, NH3 concentration, but propionate increased by monensin. Blood urea nitrogen was increased linearly by monensin. There was a quadratic effect of monensin on N intake. Monensin had a quadratic effect on milk yield, whereas 3.5% FCM was decreased linearly. These results suggest that monensin improves performance of mid-lactating dairy cows fed corn silage-based diet, and monensin can be added up to 24 mg/kg of DM diets.